2017
DOI: 10.17951/pjss.2016.49.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Soil Conservation by Vegetative Systems in Oil Palm Cultivation

Abstract: In Indonesia, agricultural land for oil palm plantation is mostly placed on slope areas. Erosion carries down surface soil layers which are generally fertile and rich in organic matter and nutrients, causing the loss of plant nutrients. Cover crops provide protection against the destruction of soil aggregates by rain and runoff. This research aims to study the effectiveness of vegetation as soil conservation in controlling erosion and runoff. This study was a field experiment on erosion plots of 10 m × 5 m wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…We found several studies comparing changes or evaluating soil properties in forests and oil palm(Nelson et al 2014, Allen et al 2015, Sumarga et al 2016, Kenye et al 2019, Khasanah and van Noordwijk 2019, Swails et al 2019, Merten et al 2020), agroforest usually involving rubber (Bruun et al 2013, Couwenberg and Hooijer 2013, Allen et al 2015, Guillaume et al 2016, Hermawan et al 2019, Kenye et al 2019, Khasanah and van Noordwijk 2019,Merten et al 2020), and few studies evaluating changes in soils due to the transition from pastures(Nelson et al 2014, Goodrick et al 2015, Quezada et al 2019. We also found literature addressing the impact of different management practices such as using various understory vegetation(Satriawan et al 2016, Wawan et al 2019, Rahman et al 2021 and enhancing infiltration rates(Tarigan et al 2016, Damiani et al 2020.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…We found several studies comparing changes or evaluating soil properties in forests and oil palm(Nelson et al 2014, Allen et al 2015, Sumarga et al 2016, Kenye et al 2019, Khasanah and van Noordwijk 2019, Swails et al 2019, Merten et al 2020), agroforest usually involving rubber (Bruun et al 2013, Couwenberg and Hooijer 2013, Allen et al 2015, Guillaume et al 2016, Hermawan et al 2019, Kenye et al 2019, Khasanah and van Noordwijk 2019,Merten et al 2020), and few studies evaluating changes in soils due to the transition from pastures(Nelson et al 2014, Goodrick et al 2015, Quezada et al 2019. We also found literature addressing the impact of different management practices such as using various understory vegetation(Satriawan et al 2016, Wawan et al 2019, Rahman et al 2021 and enhancing infiltration rates(Tarigan et al 2016, Damiani et al 2020.…”
supporting
confidence: 50%
“…The runoff coefficient in oil palm plantations decreased from 63% to 50% when a combination of frond piles and silt pits was used as a mitigation strategy (Tarigan et al 2016). Different understory vegetation can be planted to prevent changes in infiltration and runoff, and losses of fertile soils that are rich in organic matter (Satriawan et al 2016). Preserving or planting riparian zones contributes to decreasing stream temperature (Luke et al 2017, Chellaiah andYule 2018a), bank erosion while increasing oil palm yield (Horton et al 2018), and to increasing microbial activity (Chelliah and Yule 2018b) near oil palm plantations.…”
Section: Fluvial Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings on P-uptake by Mucuna bracteate reveals that the naturally grown Mucuna bracteata took less P (6.81 mg/kg) compared to those purposely planted (10.92 mg/kg) [31]. In another study, the finding showed the potential of Mucuna bracteata as soil conservation treatment as it can take much of P which loss via sediment run-off [39].…”
Section: Effects Of Leguminous Cover Crops (Lccs) On Soil Macronutrie...mentioning
confidence: 91%